Endocrine therapy for endometrial cancer: traditional approaches and novel targets - XiaoJing Guan; RongRong Tang; JianHua Yang (Frontiers in Oncology)
Recently, the global incidence of endometrial cancer is increasing. Endocrine therapy offers advantages in the management of this malignancy due to its broad applicability and favorable tolerability profile. Although conventional endocrine treatments, including progesterone, gonadotropin-releasing hormone agonists and aromatase inhibitors demonstrate efficacy in endometrial cancer, their long-term utility is limited by adverse effects such as drug resistance and disease recurrence with prolonged treatment. Novel endocrine therapeutic agents, including selective estrogen receptor modulators, selective estrogen receptor degraders, epigenetic-targeted therapies, mTOR inhibitors, cyclin-dependent kinase inhibitors, and metformin, remain in preclinical development or clinical trials. Inspiringly, the preliminary findings suggest these emerging agents may positively impact survival outcomes in endometrial cancer patients. This review examines the mechanisms, methodologies, and efficacy of both traditional and novel endocrine therapeutic approaches for endometrial cancer.